Hibridação molecular de chalconas e análogos de neolignanas com potencial atividade antineoplásica - Fernandes, Fernanda de Sousa (2021)
The search for bioactive chemical substances, both natural and synthetic, starts from the same assumption: the reduction of the side effects caused by the drugs and increasing the effectiveness of the drug to its biological target. Same that several researches have been conducted for the synthesis of chalcones, neolignans and their analogues, there is not, so far, in the main databases used in this research, studies that have used these two classes of molecules coupled in the form of a hybrid on different therapeutic targets. The first stage of work consisted of synthesizing the reaction precursors, including 2-bromo-1-phenylethanone and 22 chalcones (2-hydroxychalcones, 3-hydroxychalcones and 4-hydroxychalcones) in which yields ranging from 15 to 100% were obtained. In possession of the different chalconas, the study of the reaction conditions that gave rise to the new analogue hybrids of 8,4'-oxyneolignans. Of the tested chalcones, those that showed promising results were the 3-hydroxychalcones and the 4-hydroxychalcones, obtaining 14 new hybrid molecules in yields ranging from 18 to 83%. The hybrid molecules synthesized had their properties biological agents evaluated for cytotoxic effects and the concentration that caused 50% of cell growth inhibition (IC50) in tumor cell lines of human glioblastoma (SNB-19), colon (HCT-116), prostate (PC-3) and leukemia acute promyelocytic (HL-60). The results of the cytotoxicity assay showed that 12 compounds (among the 14 tested) showed a percentage of inhibition of promising cell growth (≥75% cell inhibition). Compounds 67-80 were selected and the IC50 assay was evaluated revealing a moderate inhibition profile for compounds that present the chalcone moiety with groups that decrease the electronic density of the ring (deactivators), with compound 73 having the lowest IC50, for this methodology. Structural modifications of analogous compounds do not led to significant increases in cytotoxic activity when compared to the drug reference doxorubicin.